(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
India is the largest democracy on the planet. It is often said that India is a country of villages. Village is the spirit of India, without which it can’t endure. While the urban population has significantly increased in the course of the most recent few decades, the rural economy and life is integral to India’s presence and character. Village or village society didn’t spring up out of nowhere, yet they developed gradually because of change with environment. On the planet the people of different parts lead different types of lives. Their native place has direct effect of their methods of living which are as different as their attitudes. In everywhere throughout the world the people are partitioned into two distinct groups-Urban and Rural. The village is presumably the most noteworthy unit of Indian society. It is where the entirety of rural life unfurls itself and capacities. To an Indian, a village implies numerous things. On its definition stands the political state of the nation on its understanding depends the economic advancement of the country. The depiction of an Indian village implies, as a result, the portrayal of the very essence of the nation. An Indian village is in actuality the reflection of India, of both the past and the present, and on its future depends the eventual fate of the country. The significance of the village in India’s socio-political life has been foremost to such an extent that it has even prompted the conceptualisation of another political hypothesis - ’Villagism’- in India (Prasad, 2003 16 1).